The Contribution of Personality, Work Motivation Toward Organizational Commitment and Performance of the Academic Staff - Ni Kadek Ani Widiani; Nengah Landra; Anik Yuesti; Putu Kepramareni (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2023)
This research aims at measuring the contribution of personality, work motivation toward organi-zational commitment and performance among academic staff of a private higher education institution at Universitas Mahasaraswati Denpasar (Unmas Denpasar). This research uses observational analytic approach, the sampling technique used is saturated sampling by taking all the population as the research sample which is 140 respondents. The analysis technique is using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The result of the research shows that the personality of the acade-mic staff at Unmas Denpasar does not affect the organizational commitment. The high level of motivation might improve organizational commitment, in addition, personality score and high motivation may im-prove performance of the academic staff at Unmas Denpasar. Nevertheless, organizational commitment of the academic staff does not influence performance. The test of indirect influence shows that the va-riable of organization commitment does not mediate the effect of personality and motivation toward performance.